Incidencia del virus del amarillamiento de venas en papa en el Ecuador y su transmisión a través de los tubérculos - Díaz M, J. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Potato yellow vein virus occurs in the highlands of Ecuador, and affects the most common varieties. On the Curipamba variety vein yellowing appears indistinctly at the age of three months in the upper, intermediate and lower leaves, and as the plant grows, it becomes more conspicuous in the rest of the leaves which appeared healthy before. Increase of infected plants in the fields is in direct proportion to the age, although the virus can make itself. The tuber production is reduced 40–50% in weight. Prior to transmission studies, groups of infected and healthy plants were marked in the field and harvested repeatedly. These tubers were planted at the greenhouse in separated pots, and plant infection was recorded periodically. The Curipamba variety gave 50% transmission, Rosada with purple eyes 75%, and Rosada with white eyes 60%, as compared with 3.3% of the healthy groups. In a second planting, plants which were selected as healthy or infected in the field, continued being healthy or infected, but rarely the infected groups gave healthy plants in the second planting. Conversely, some of the plants coming from infected tubers did not show the disease during the first planting and gave positive reaction on the second one. It seems that the virus is poorly distributed in the plant and in the tubers.